Optimizing Accounting and Auditing Principles: A Fuzzy MCDM Approach to Ranking Key Influencing Factors - Weiwen Wang; Jiajia Pan; Jinjin Pan; Qiang Guo; Desong Kong; Zhuo Sun (IEEE Access)
Accounting and auditing principles ensure financial transparency, regulatory compliance, and efficient decision-making in organizations. These principles face constant impact from such uncertainties as changing financial regulations, subjective expert decisions, and complicated financial information. This research creates a multi-criteria decision-making (MCDM) approach linking step-wise weight assessment ratio analysis (SWARA) with combined compromise solution (CoCoSo) through complex spherical fuzzy sets (CSFS) to handle existing uncertainties. Through this approach, decision-makers can make more precise choices because it successfully measures expert evaluation ambiguity and imprecision. Three decision-makers prioritize accounting and auditing alternatives by considering key evaluation criteria, including international financial reporting standards (IFRS) compliance, accuracy, cost efficiency implementation, ease of risk mitigation, data security, and adaptability. Internal control mechanisms ( $A_{10}$ ) maintained the most preferred position in the results because they demonstrate fundamental importance for financial governance. The sensitivity analysis of the ranking system shows that changes in parameter values do not affect the stability of the proposed method. The proposed method outperforms other MCDM techniques regarding calculation speed and improved decision quality. The SWARA-CoCoSo approach is an optimal auditing solution in the CSFS, as shown by the research findings guiding policymakers, financial institutions, and regulators to implement the most resilient audit strategies.